2000
DOI: 10.1523/jneurosci.20-04-01568.2000
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Induces Impairment of Spatial Working Memory Because of Prefrontal Dopaminergic Dysfunction

Abstract: Although the mechanism responsible for cognitive deficits in stress-related neuropsychiatric disorders has been obscure, prefrontal cortical (PFC) dopaminergic dysfunction is thought to be involved. In animals, the mesoprefrontal dopaminergic system is particularly vulnerable to stress, and chronic stress induces working memory impairment. However, the relation between the working memory impairment and altered dopaminergic activity in chronically stressed rats is unclear. Furthermore, the change of dopaminergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
263
3
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(288 citation statements)
references
References 51 publications
18
263
3
4
Order By: Relevance
“…On the other hand, the effects of a variety of stressors on extracellular DA levels in the PFC and NAc have been relatively well-characterized. These studies have shown that chronic or repeated exposure to a stressor results in no change or a slight decrease in basal extracellular DA in the PFC and/or NAc (Finlay et al 1995;Gresch et al 1994;Imperato et al 1992Imperato et al , 1993Mizoguchi et al 2000). Consistent with this, while cold stress reliably induces an increase in NE neuron excitability in the LC (Jedema et al 2001;Mana and Grace 1997), it produces a decrease in active DA neurons.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…On the other hand, the effects of a variety of stressors on extracellular DA levels in the PFC and NAc have been relatively well-characterized. These studies have shown that chronic or repeated exposure to a stressor results in no change or a slight decrease in basal extracellular DA in the PFC and/or NAc (Finlay et al 1995;Gresch et al 1994;Imperato et al 1992Imperato et al , 1993Mizoguchi et al 2000). Consistent with this, while cold stress reliably induces an increase in NE neuron excitability in the LC (Jedema et al 2001;Mana and Grace 1997), it produces a decrease in active DA neurons.…”
mentioning
confidence: 62%
“…Although the changes in mesoaccumbens and mesocortical DA transmission following acute exposure to a stressor have been well characterized, less is known about the response of these systems to chronic stress or exposure to highly traumatic conditions. However, there is evidence that DA release in the NAc and PFC may show some adaptation to the stressor after repeated (Cabib and Puglisi-Allegra 1996;Imperato et al 1992Imperato et al , 1993 or chronic (Gresch et al 1994;Mizoguchi et al 2000) exposure. Finlay et al (1995) have shown that following chronic exposure to inescapable cold, considered a chronic stressor, extracellular DA levels in the NAc and PFC are unchanged or slightly lower than in controls (Gresch et al 1994).…”
mentioning
confidence: 99%
“…1 A ), as described previously (Sugama et al., 2009). This stress protocol has been widely used to study the effects of stress, including ulcers (Kato et al., 1998) and memory impairment (Mizoguchi et al., 2000). The rats were sacrificed immediately following the conclusion of the stressor, and trunk blood was collected.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that cocaine withdrawal is associated with low dopaminergic tone in the dmPFC (Sorg et al, 1997;Williams and Steketee, 2005), and that low dopaminergic tone in the dmPFC induces working memory impairments in this task (Mizoguchi et al, 2000;Simon et al, 1980), it is likely that the working memory impairments observed in LgA rats resulted from both decreased dopaminergic tone and a decreased number of neurons/oligodendrocytes in the dmPFC. Similar neural changes may be responsible for the cognitive impairments observed in humans with drug addiction (Goldstein and Volkow, 2002;Pfefferbaum et al, 1998;Bechara, 2005;Franklin et al, 2002;Jentsch and Taylor, 1999;Rogers and Robbins, 2001).…”
Section: Discussionmentioning
confidence: 99%